2017
DOI: 10.1167/iovs.17-21461
|View full text |Cite
|
Sign up to set email alerts
|

Macular Vascular Fractal Dimension in the Deep Capillary Layer as an Early Indicator of Microvascular Loss for Retinopathy in Type 2 Diabetic Patients

Abstract: Citation: Chen Q, Ma Q, Wu C, et al. Macular vascular fractal dimension in the deep capillary layer as an early indicator of microvascular loss for retinopathy in type 2 diabetic patients. Invest Ophthalmol Vis Sci. 2017;58:3785-3794. DOI:10.1167/ iovs.17-21461 PURPOSE. To determine the ability of fractal dimension to detect early changes in the retinal microvascular network imaged by optical coherence tomography angiography (OCT-A) in type 2 diabetic patients. METHODS.Sixty-seven patients with type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 31 publications
14
76
1
Order By: Relevance
“…22 Fractal analysis has already been used to explore the retinal vasculature in several studies, using fundus photography, [23][24][25][26] FA, 27,28 or OCT-A. 29,30 To the best of our knowledge, there is no anatomic data available, analyzing the effects of physical exercise in healthy subjects, on the retinal VDs, FAZ area, and retinal vascular FD in vivo using OCT-A at the same time. Variations in microretinal vasculature, which might be expected, could have an impact on the results of the examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Fractal analysis has already been used to explore the retinal vasculature in several studies, using fundus photography, [23][24][25][26] FA, 27,28 or OCT-A. 29,30 To the best of our knowledge, there is no anatomic data available, analyzing the effects of physical exercise in healthy subjects, on the retinal VDs, FAZ area, and retinal vascular FD in vivo using OCT-A at the same time. Variations in microretinal vasculature, which might be expected, could have an impact on the results of the examination.…”
Section: Methodsmentioning
confidence: 99%
“…The OCT-A SCP and DCP flow images generated by automatic segmentation were extracted in raw format and further processed with ImageJ (http://imagej.nih.gov/ij/; Wayne Rasband, provided in the public domain by the National Institutes of Health, Bethesda, MD, USA). We used the macro design described in a previous study 31 and applied it into all OCT-A images.…”
Section: Fractal Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found a significantly decreased vessel density in both superficial and deep vascular layers in patients without DR [7, 9]; however, in three other reports, vessel density was significantly reduced only in the deep vascular layer [10-12]. Fractal dimension was also significantly reduced in both superficial and deep vascular layers of patients with type 2 diabetes without DR [13]. The number of microaneurysms in the deep vascular layer exceeded the number in the superficial vascular layer in patients with nonproliferative DR (NPDR) [14-16].…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
“…The macular nonperfusion area was significantly increased in both superficial and deep vascular layers in patients with NPDR compared to control subjects [14, 22]. Fractal dimension in patients with NPDR was decreased in both retinal vascular layers compared to control subjects [13, 25, 27]. In contrast, another group reported increased fractal dimension in both vascular layers of patients with NPDR compared to control subjects [23].…”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%